A web-based model to enhance algorithmic thinking for novice programmers. (1st November 2021) - Iqbal Malik, Sohail; Mathew, Roy; Tawafak, Ragad M; Alfarsi, Ghaliya
Algorithmic thinking is considered as one of the important steps toward learning to code for novices in programming education. In this study, algorithmic thinking was promoted by introducing a Problem Analysis Algorithmic Model (PAAM) in an Algorithms and Programming 1 (AP) course. A web-based application is developed to offer the PAAM model in the course. The application includes all teaching topics taught in the AP course. One-way cluster sampling and quantitative research were used in this research study. The impact of the PAAM model on novices was determined by conducting a survey. t-test was performed to analyze the students' responses. The final exam grades for the last two semesters were compared to examine the effect of the PAAM model on students' gain in the AP course. Results show that novice programmers appreciated the PAAM model in the AP course teaching processes and learning activities. The model supports novices to understand the programming question requirements (input, process, and output) and promotes algorithmic thinking. Moreover, the model helps students in learning problem-solving skills, understanding programming concepts and structures. It also focuses on students' cognitive engagement and gain in programming. The model not only impacts positively on students' gain but it also helps in reducing the attrition rates (failure and dropout) in the course.